Physicochemical Properties and Consumer Preference of Fish Burgers Produced from Black Tilapia Surimi Paste and Potato Flour - Fairus Abdul Manaf; Nur Huda Faujan; Norlelawati Arifin; Norbalqis Bukhary Mohd Hanafiah (Universiti Sains Islam Malaysia, 2024)
This study was conducted to evaluate the physicochemical characteristics and to determine the degree of consumer preference of fish burgers produced with different level of Black Tilapia surimi paste and potato flour. Five formulation of fish burgers with different percentage of Black Tilapia surimi paste to potato flour were formulated as follows: Control=70:10; A=62:18; B=66:14; C=74:6; D=78:2. The fish burgers were analysed for their colour, cooking loss, texture, pH, water holding capacity, and folding test as well as the proximate composition. Hedonic test was also carried out to evaluate the consumer preference of the fish burgers. In term of colour, raw fish burgers of formulation A was the highest (P<0.05) in the value of whiteness (L*), redness (a*), and yellowness(b*). In addition, both raw and cooked fish burger of formulation A was also significantly the highest (P<0.05) in the hardness between all formulations. However, proximate composition of raw and cooked fish burger of formulation D which contained the highest of percentage of Black Tilapia surimi paste to potato flour was significantly highest (P<0.05) in moisture and protein content. The preferenceof panellists within formulations were not significantly differed (P>0.05) in attributes of appearance, fish aroma, texture, taste, and overall acceptance except for juiciness (P<0.05). Thus, this study concluded that fish burgers produced from Black Tilapia surimi paste combining with potato flour at different level affected physicochemical properties of fish burgers but did not affect consumer acceptability.